Evaluation of marginal and internal gaps of Ni-Cr and Co-Cr alloy copings manufactured by microstereolithography - Kim, Dong-Yeon (J Adv Prosthodont, 2017)
PURPOSE: The purpose of this study was to evaluate the marginal and internal gaps of Ni-Cr and Co-Cr copings, fabricated using the dental µ-SLA system. MATERIALS AND METHODS: Ten study dies were made using a two-step silicone impression with a dental stone (type IV) from the master die of a tooth. Ni-Cr (NC group) and Co-Cr (CC group) alloy copings were designed using a dental scanner, CAD software, resin coping, and casting process. In addition, 10 Ni-Cr alloy copings were manufactured using the lost-wax technique (LW group). The marginal and internal gaps in the 3 groups were measured using a digital microscope (160 ×) with the silicone replica technique, and the obtained data were analyzed using the non-parametric Kruskal-Wallis H test. Post-hoc comparisons were performed using Bonferroni-corrected Mann-Whitney U tests (α=.05). RESULTS: The mean (±standard deviation) values of the marginal, chamfer, axial wall, and occlusal gaps in the 3 groups were as follows: 81.5±73.8, 98.1±76.1, 87.1±44.8, and 146.8±78.7 µm in the LW group; 76.8±48.0, 141.7±57.1, 80.7±47.5, and 194.69±63.8 µm in the NC group; and 124.2±52.0, 199.5±71.0, 67.1±37.6, and 244.5±58.9 µm in the CC group. CONCLUSION: The marginal gap in the LW and NC groups were clinically acceptable. Further improvement is needed for CC group to be used clinical practice.